DISPOSITION ANALYSIS OF ELEMENTARY SCHOOL STUDENTS IN MATHEMATICAL PROBLEM SOLVING - Riandi Marisa; Yulia Santi; Ety Mukhlesi Yeni; Sri Dewi Nirmala (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The role of students' attitudes (disposition) towards mathematics is an important element in solving mathematical problems and must be maximized properly. Disposition has the following indicators: self-confident, flexibility, persistent, curiosity, reflecting, apply it. This study aims to describe the elementary students' mathematical disposition profile towards problem solving abilities. The research method uses qualitative-descriptive. Data were collected through questionnaires, observations, and interviews then analyzed by triangulation technique. The results show that there is a significant relationship between elementary school students' mathematical dispositions to problem solving abilities. Students who meet the